(3GddOGFf GdebSGI HGdMQGQI (B/s - (3NdjaI, SdjeGfs ((3OeTb (B:s (3OGQ OeTb ddWHGYI hGdfTQ hGdJhRjY,s, 1996)
(3eONd Edi Yde GdHdGSJjc(B-(3GdehGO GdHdGSJjcjI GdeJUdHI MQGQjG(B-(3GdBdjd(B-(3GdHjSeGd EjejO(B-(3GdCjHhcSj(B-(3Gdajfhdjc(B-(3GdHhdj ESJQ GdeJUdH MQGQjG(B-(3GdHhdj EjejO GdeJUdH MQGQjG(B-(3GdHhdj jhQjKGf GdeJUdH MQGQjG(B-(3GdSjdjchf(B-(3GdjhQjG(B-(3hGdejdGejf ahQeGdOjgjO(B-(3GdCdcjO(B-(3GdHhdj HhJGOjf(B-(3Odjd GdTQcGJ GdCeQjcjI GdUGfYI hGdeehdI dehGO GdHdGSJjc GdeJUdH MQGQjG(B-(3Odjd GdTQcGJ GdCeQjcjI GdUGfYI hGdeehdI dBdGJ GdbhdHI HGdVZW hGdJMhjd(B.s
(3jTJed Ydi bGFeI HGdeUWdMGJ GdafjI HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
(3jTJed Ydi edGMb(B.s
(3HHdjhLQGajI (B: (3U(B. 274.s
Keywords: (3GdHdGSJjc GdMQGQjs; (3UfGYI hJLGQI GdHdGSJjcs; (3GdHdGSJjcs -- (3VHW LhOIs